LEGAL ASPECT OF CORPORATE ACTIONS ON TELECOMMUNICATION OPERATORS FOR UTILIZING RADIO FREQUENCY SPECTRUM - Mohan Rifqo Virhani (Puslitbang Literasi dan Profesi SDM Komunikasi dan Informatika, 2015)
This research describe legal aspect of corporate actions such as merger, consolidation and acquisition of telecommunication operators who are utilizing radio frequency spectrum in Indonesia. Telco operators’ corporate actions should be carried out to enable utilization of radio frequency spectrum efficiently and effectively. Radio frequency spectrum utilization effectively and efficiently conducted through legal enforcement of single preserence policy on telecommunication sector (single ownership) whereas only one party would be the controlling shareholder in 1 (one) legal entity of telco provider. This legal enforcement is one way to restructure the telecommunication industry to achieve an ideal structure. The implementation of law of single preserence policy on telecommunication sector should oblige to other law and regulations pertinent to corporate laws, telecommunication laws and anti monopoly law.Keywords: corporate actions, single preserence policy on telecommunication sector, radio frequency spectrum, anti monopoly law